2014
DOI: 10.1350/pojo.2014.87.3.676
|View full text |Cite
|
Sign up to set email alerts
|

Police Stressors, Negative Outcomes Associated with Them and Coping Mechanisms That May Reduce These Associations

Abstract: One purpose of the present study was to examine how exposure to police stressors was associated with increased risk for physical, psychological and interpersonal negative outcomes. Another purpose was to identify ‘healthy’ or ‘unhealthy’ coping mechanisms that mediate these associations between police stressors and negative outcomes. Participants included 201 police officers from small departments under 100 officers (96% male; mean age = 40.3 years; 91% Caucasian; 55% Patrol Officer rank; mean years of servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…More specifically, for both gay men and lesbian women in the present study, repressed anger was the only coping behavior significantly associated with exposure to sexual minority stressors (harassment and concealment for gay men, concealment for lesbian women), with repressed anger found to be a significant mediator between exposure to these sexual minority stressors and three negative psychological outcomes (health concerns, poor self-esteem, PTSD symptoms). Present results with sexual minority individuals correspond with those from research documenting more negative psychological outcomes for mostly heterosexual samples of police officers and university employees, for whom repressed anger was also found to mediate associations between workplace social stressors and negative psychological outcomes such as health concerns, poor self-esteem, PTSD, poor job satisfaction, and interpersonal conflict (Can & Hendy, 2014;Hendy, Can, Covell, & Keating, submitted manuscript).…”
Section: Discussionsupporting
confidence: 84%
“…More specifically, for both gay men and lesbian women in the present study, repressed anger was the only coping behavior significantly associated with exposure to sexual minority stressors (harassment and concealment for gay men, concealment for lesbian women), with repressed anger found to be a significant mediator between exposure to these sexual minority stressors and three negative psychological outcomes (health concerns, poor self-esteem, PTSD symptoms). Present results with sexual minority individuals correspond with those from research documenting more negative psychological outcomes for mostly heterosexual samples of police officers and university employees, for whom repressed anger was also found to mediate associations between workplace social stressors and negative psychological outcomes such as health concerns, poor self-esteem, PTSD, poor job satisfaction, and interpersonal conflict (Can & Hendy, 2014;Hendy, Can, Covell, & Keating, submitted manuscript).…”
Section: Discussionsupporting
confidence: 84%
“…The organizational and operational stressors that police officers regularly face can be associated with negative mental health outcomes (van der Velden, Kleber, Grievink, & Yzermans, 2010) including depression (Wang et al, 2010), maladaptive coping strategies (i.e. anger repression; Hakan Can & Hendy, 2014), and posttraumatic stress disorder (PTSD) (Maguen et al, 2009), as well as risk for physical health problems, burnout, smoking, sleep disorders, alcohol abuse, and suicide ideation (Anshel, 2000;Brown & Campbell, 1994;Gershon, Barocas, Canton, Li, & Vlahov, 2009;Karaffa & Koch, 2016;Waters & Ussery, 2007). Karaffa and Koch (2016, p. 760) reported that "the accumulation of stress can overwhelm even the most resilient officers".…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate use of force is a necessary component of successful policing; however, psychologically impaired LEOs are more likely to use excessive force (Kop et al, 1999; Kurtz et al, 2015; Nieuwenhuys et al, 2012b), be aggressive toward suspects (Can and Hendy, 2014; Gershon et al, 2009; Griffin and Bernard, 2003; Kurtz et al, 2015; Rajaratnam et al, 2011), and exhibit poor decision-making (Nieuwenhuys et al, 2012a; Rajaratnam et al, 2011; Violanti et al, 2014). Bureau of Justice Statistics (https://www.bjs.gov) estimates that among 59.4 million U.S. residents age 16 or older who had face-to-face contacts with police, 2.3 million experienced LEO threat or use of force, and nearly 75% of those who reported force described it as excessive (Berzofsky, 2017).…”
Section: Introductionmentioning
confidence: 99%